COVID-19 Social Distancing and Online Mutual Help Engagement for Alcohol Use Recovery. Issue 6 (November 2021) - Colditz, Jason B.; Rothenberger, Scott D.; Liebschutz, Jane M.; Rollman, Bruce L.; Kraemer, Kevin L.
Abstract : Introduction: COVID-19 and associated social distancing has presented challenges for individuals engaging in face-to-face mutual help groups (MHGs) such as Alcoholics Anonymous for alcohol use recovery. Online MHGs may be particularly appealing to individuals with limited access or inclination to attend in-person MHGs. We examined engagement within the popular "StopDrinking" online MHG, hypothesizing that engagement would increase due to demand for virtual peer support as COVID-19 social distancing progressed. Methods: We collected publicly available engagement data for StopDrinking from February 19, 2018 through April 30, 2020 while considering March and April of 2020 as months initially impacted by voluntary or mandated COVID-19 social distancing. Using seasonal autoregressive integrated moving average models, we predicted daily engagement for this social distancing time period based on all available engagement data collected before April 2020. Kalman filtering with 95% prediction limits was employed to define significant thresholds for observed data to reside within. Results: All days of observed engagement in March and April 2020 were lower than corresponding predicted values. Observed engagement fell below the lower 95% prediction limit for 36% of days, with 15 days in March and 7 days in April having significantly lower than predicted engagement. Conclusions: Relatively low activity on StopDrinking may signal broader population trends of problematic alcohol use and recovery disengagement during the initial COVID-19 social distancing timeframe. Continued investigation of online MHGs is needed to understand their potential for monitoring population health trends and to understand how such groups might support alcohol use recovery in contexts of crisis and isolation.